Abnormalities of interhemispheric functional connectivity in individuals with acute eye pain: a resting-state fMRI study - Dong, Zhi-Zhang (Int J Ophthalmol, 2019)
AIM: To study the changes of the resting state functional connectivity (rsFC) between acute eye pain (EP) subjects and healthy controls (HCs) in the two hemispheres by using voxel-mirrored homotopic connectivity (VMHC) method. METHODS: Totally 20 patients with EP and 20 HCs were enrolled, sex, age, and education were matched, and all subjects were examined by functional magnetic resonance imaging (fMRI) scans at resting-state. The changes of rsFC between the hemispheres were evaluated by the VMHC method according to Gaussian random field (GRF) theory. In order to identify the VMHC, as biomarkers for distinguishing EP and from HC, the receiver operating characteristic curves (ROC) had been analyzed. The relationships were evaluated with Pearson correlation analysis between the mean VMHC signal values and clinical features in these patients. RESULTS: By comparing with health subjects, the significant decreased VMHC values was observed in lingual/calcarine (Brodmann area, BA 30), precentral/postcentral gyrus (PreCG/PosCG; BA 4) and medial frontal gyrus (MFG; BA 8) (false discovery rate corrected <0.01) in the acute EP individuals. The accuracy of area under curve was excellent indicated by the ROC curve analysis of each brain regions. CONCLUSION: Our study demonstrates preliminary evidence of disrupted interhemispheric rsFC in acute EP in sensorimotor and limbic system and somatosensory cortex, which might give some useful information for understanding the neurological mechanisms in acute EP individuals.